1990
DOI: 10.1126/science.250.4983.973
|View full text |Cite|
|
Sign up to set email alerts
|

Ice Nucleation by Alcohols Arranged in Monolayers at the Surface of Water Drops

Abstract: Monolayers of aliphatic long-chain alcohols induced nucleation of ice at temperatures approaching 0 degrees C, in contrast with water-soluble alcohols, which are effective antifreeze agents. The corresponding fatty acids, or alcohols with bulky hydrophobic groups, induce freezing at temperatures as much as 12 degrees C lower. The freezing point induced by the amphiphilic alcohols was sensitive not only to surface area per molecule but, for the aliphatic series (C(n)H(2n + 1)OH), to chain length and parity. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
191
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(213 citation statements)
references
References 20 publications
21
191
0
1
Order By: Relevance
“…The SFG spectrum of a water surface covered by a full monolayer in Figure 3 is also quite interesting. It has recently be shown that such a monolayer on water is able to induce an increase of the icing temperature of the nearby water because of the ordered OH groups in the alcohol monolayer closely match those of the hexagonal ice layer in the a-b plane [11]. The similarity of our spectrum of the air-alcohol-water interface and the SFG spectrum of quartz-Ice surface, shown in Fig.…”
Section: Air-water Interfacesupporting
confidence: 68%
“…The SFG spectrum of a water surface covered by a full monolayer in Figure 3 is also quite interesting. It has recently be shown that such a monolayer on water is able to induce an increase of the icing temperature of the nearby water because of the ordered OH groups in the alcohol monolayer closely match those of the hexagonal ice layer in the a-b plane [11]. The similarity of our spectrum of the air-alcohol-water interface and the SFG spectrum of quartz-Ice surface, shown in Fig.…”
Section: Air-water Interfacesupporting
confidence: 68%
“…This suggests that the alcohol monolayer, is capable of inducing a surface water structure more ordered like ice. That this is indeed possible has been pointed out by Gavish et al (45). They realize that the lattice structure of the alcohol monolayer matches fairly well with that of hexagonal ice, rendering ice nucleation by epitaxial induction under the alcohol monolayer possible.…”
mentioning
confidence: 67%
“…Crystals of some sterols, for example, trigger nucleation > −5 • C, although the fungal sterol ergosterol and the plant sterol β-sitosterol were found to be inactive (Head, 1962;Fukuta and Mason, 1963). Under optimal conditions, monolayers of aliphatic alcohols can also induce ice nucleation at temperatures ranging from ≈ −14 • C for C 14 H 29 OH to just below −1 • C for C 31 H 63 OH (Gavish et al, 1990;Popovitz-Biro et al, 1994; see also Rosinski, 1980). Nucleation is facilitated by alcohols self-assembling into two-dimensional crystalline clusters on air : liquid or liquid : liquid interfaces, with their hydroxyl groups embedded into the water surface and arrayed with a spacing closely matching hexagonal ice (Gavish et al, 1990;Popovitz-Biro et al, 1991).…”
Section: Inps From Sterols and Monolayers Of Aliphatic Alcoholsmentioning
confidence: 99%
“…Under optimal conditions, monolayers of aliphatic alcohols can also induce ice nucleation at temperatures ranging from ≈ −14 • C for C 14 H 29 OH to just below −1 • C for C 31 H 63 OH (Gavish et al, 1990;Popovitz-Biro et al, 1994; see also Rosinski, 1980). Nucleation is facilitated by alcohols self-assembling into two-dimensional crystalline clusters on air : liquid or liquid : liquid interfaces, with their hydroxyl groups embedded into the water surface and arrayed with a spacing closely matching hexagonal ice (Gavish et al, 1990;Popovitz-Biro et al, 1991). In the two soils tested here, the removal of organics with chloroform had no significant effect upon the INP spectra (Fig.…”
Section: Inps From Sterols and Monolayers Of Aliphatic Alcoholsmentioning
confidence: 99%